PERSEPSI PETANI KAKAO TERHADAP TEKNIK SAMBUNG SAMPING DI DESA BATU LAPPA, SULAWESI SELATAN - Galib Suwito Cora; Didi Rukmana; A Amrullah (Jurnal Sosial Ekonomi Pertanian, 2018)
AbstractThe research was aimed to: (1) describe factors that affected farmers’ perception toward side-grafting technique; (2) to analyze the level of cacao farmers’ perception toward side-grafting  technique which include technique and results of side-grafting, (3) to analyze the relationship among factors of perception formulation with technique and results of side-grafting. The research was used quatitative methods . The data was collected by quetionnaire. The research showed that; (1) factors that formed perception include age, formal education, non-formal education, farming experience, accessibility on information, and social environment, (2) the level of farmer’s  perception toward side-grafting technique was very good with score 4,48 and toward results of side-grafting also was very good with score 4,23; (3) it was showed that there were relationship among non-formal education, accessibility on information with farmer’s percepcion toward side-grafting technique. Also, there were relationsip  among non-formal education toward results of side-grafting. Keywords: perception; cacoa farmer; side-grafting; step of side-grafting; results of side-grafting